1992
DOI: 10.7326/0003-4819-116-6-446
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sympathetic Nervous Activity and the Effects of Its Inhibition with Clonidine in Alcoholic Cirrhosis

Abstract: The sympathetic nerves to the kidneys, heart, and hepatomesenteric circulation are stimulated in patients with cirrhosis. Clonidine inhibits these activated sympathetic outflows differentially, which could possibly provide a basis for the selective pharmacologic treatment of portal hypertension in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 32 publications
4
40
1
1
Order By: Relevance
“…Although relatively few studies have evaluated this pathway in cirrhotic patients, improved renal function and lowered noradrenaline overflow from the kidney have been observed when the intrahepatic pressure is reduced in cirrhotic patients. 69,70 These observations are consistent with the notion that the hepatoportal baroreflex contributes to increased renal sympathetic nerve activity.…”
Section: Liver Cirrhosissupporting
confidence: 80%
“…Although relatively few studies have evaluated this pathway in cirrhotic patients, improved renal function and lowered noradrenaline overflow from the kidney have been observed when the intrahepatic pressure is reduced in cirrhotic patients. 69,70 These observations are consistent with the notion that the hepatoportal baroreflex contributes to increased renal sympathetic nerve activity.…”
Section: Liver Cirrhosissupporting
confidence: 80%
“…Persistent cardiac sympathetic activation is present in patients with depressive illness 40 and cirrhosis, 43 where it is thought to be harmful. Cardiac sympathetic stimulation is at a high level in heart failure, 44,45 where it is known with certainty to be harmful, 19 and countered with β-adrenergic blockade.…”
Section: Potential Neural Mechanisms Of Toxicity Of the Sympathetic Pmentioning
confidence: 99%
“…Some supportive evidence to this contention already exists in alcoholic cirrhosis, another disease model of sympathetic overactivation. In this condition, Esler et al 21 have previously demonstrated that sympathetic outflow to the hepatomesenteric circulation was more sensitive to pharmacological suppression with clonidine than was the systemic sympathetic outflow. Although the cardiac effects of sympathoinhibitory treatments in CHF have been previously studied, [12][13][14] little work has been performed with regards to renal sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although the effects of carvedilol on cardiac and systemic sympathetic activity have been studied, 24 possible effects on renal sympathetic tone remain to be investigated. In hepatic cirrhosis, Esler et al 21 have demonstrated increased sympathetic neural outflow to the kidneys in humans, with a reduction in renal sympathetic tone and an increase in glomerular filtration rate with intravenous clonidine. However, to our knowledge, the effects of clonidine on renal sympathetic tone in human CHF have not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%